EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DALAM PENGENDALIAN INTERNAL PERUSAHAAN START UP DI JAKARTA - Haryo Sulistianto (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The study aims to assess the effectiveness of SIA in supporting internal control of start-up companies in Jakarta. Using descriptive quantitative methods, the study explores how SIA integration can affect the internal control of the company. A total of 100 start-ups in Jakarta were selected as samples through purposive sampling techniques. Data collection is carried out through a questionnaire designed to measure management perception of the effectiveness of the SIA used and implementation of internal controls. Data analysis is performed using simple descriptive analysis and linear regression techniques. Research results show that there is a significant positive link between SIA integration and the effectiveness of internal controls. Companies with an integrated SIA are experiencing an improvement in internal control. Despite this, challenges such as the cost and complexity of implementation, as well as the need for improved training for users, were identified as major obstacles. The research concludes that investment in integrated SIA development is essential to support the effectiveness of internal controls in start-ups. Recommendations for start-ups include focusing on human resource development and change management to maximize SIA’s potential.